1980
DOI: 10.1021/i260076a018
|View full text |Cite
|
Sign up to set email alerts
|

Selective Transport of Sulfur Dioxide through Polymer Membranes. 1. Polyacrylate and Cellulose Triacetate Single-Layer Membranes

Abstract: Commercial samples (75-250 µ thick) of polyacrylate and cellulose triacetate polymers were found to be selectively permeable to S02. Ultrathin films (0.05-10 µ thick) of these polymers were prepared to achieve the high S02 fluxes which are required for S02 gas separations. The results of tests with pure N2, C02, and S02 showed that N2 and C02 permeabilities were nearly independent of pressure but the S02 permeability had a large pressure dependence which adversely affected membrane performance. S02 permeation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Polymer blending for the production of new polymeric membranes is an encouragement of membrane researchers toward performance increase and characteristic enhancement of the polymeric membranes in gas separation. [10] Gas separation membranes prepared via the blending method have shown enhanced mechanical properties, better fabrication processability, and more gas permeability, and all these are favorable. A useful composition of the advantages of each polymer is accessible in a new product by blending.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer blending for the production of new polymeric membranes is an encouragement of membrane researchers toward performance increase and characteristic enhancement of the polymeric membranes in gas separation. [10] Gas separation membranes prepared via the blending method have shown enhanced mechanical properties, better fabrication processability, and more gas permeability, and all these are favorable. A useful composition of the advantages of each polymer is accessible in a new product by blending.…”
Section: Introductionmentioning
confidence: 99%
“…This intriguing behavior is mainly due to EG segments in the copolymer chains. It was reported that PEG can dissolve a substantial amount of sour gas 42. Ether groups in PEG as polar moiety groups have affinity to CO 2 gas due to dipole‐quadrupole interaction 38.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the PIM-1, polyethylene glycol (PEG) has excellent CO 2 selectivity due to the existence of large amount of ether oxygen groups in its matrix [23,24]. However, it is difficult to produce a thin membrane due to its weak mechanical and thermal strength [25].…”
Section: Introductionmentioning
confidence: 99%